2009
DOI: 10.1074/jbc.m805542200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Bcl-2 Homology 3 Domain Recognition in the Bcl-2 Protein Family

Abstract: The proteins of the Bcl-2 family are important regulators of apoptosis, or programmed cell death. These proteins regulate this fundamental biological process via the formation of heterodimers involving both pro-and anti-apoptotic family members. Disruption of the balance between anti-and pro-apoptotic Bcl-2 proteins is the cause of numerous pathologies. Bcl-xl, an anti-apoptotic protein of this family, is known to form heterodimers with multiple pro-apoptotic proteins, such as Bad, Bim, Bak, and Bid. To elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 64 publications
(83 reference statements)
5
35
1
Order By: Relevance
“…Previous point mutation studies of these two Bad peptide residues (A5G and F23A) demonstrated ∼4 fold less binding affinity compared with wild type peptide also suggests the important role of these residues for binding [36]. Previous computational study also recognized these two residues as probable hot spots of BH3 peptides for Bcl-2 family proteins binding [44]. These strong interactions of A5 and F23 could be the possible reasons for the extended alpha helical nature of the Bad peptide appeared in the Bcl-XL/Bad peptide simulation (Figure S1B).…”
Section: Discussionmentioning
confidence: 95%
“…Previous point mutation studies of these two Bad peptide residues (A5G and F23A) demonstrated ∼4 fold less binding affinity compared with wild type peptide also suggests the important role of these residues for binding [36]. Previous computational study also recognized these two residues as probable hot spots of BH3 peptides for Bcl-2 family proteins binding [44]. These strong interactions of A5 and F23 could be the possible reasons for the extended alpha helical nature of the Bad peptide appeared in the Bcl-XL/Bad peptide simulation (Figure S1B).…”
Section: Discussionmentioning
confidence: 95%
“…The BH1 domain is part of the hydrophobic groove that binds BH3 motifs [32], suggesting a BH3-mediated interaction. N136 of BCL-xL forms a hydrogen bond with a carboxylate group of the conserved D in the BH3 motif [32]. Mutation of N136 to I eliminates this and leads to loss of a stabilizing interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Of these residues, Leu 112 , Leu 116 , and Gly 120 are completely buried; Phe 123 is partially buried; the aliphatic part of the Lys 117 side chain hydrophobically packs against M11 residues Asp 81 and Arg 87 , whereas the amino group makes polar and charged interactions; and Gly 120 and Asp 121 interact with a Gly-Arg pair conserved in most Bcl-2 homologs, including Bcl-X L and M11 (21, 22, 36 -38). This Gly-Arg pair, especially the Arg, has been shown to contribute significantly to the interaction of many Bcl-2 homologs with diverse BH3 domains (19,48 The Beclin 1 BH3 domain binds with a very similar, moderate binding affinity of ϳ1.5 M to both M11 and Bcl-X L (see Table 3). Further, for both interactions, the favorable free energy of association (⌬G) is due to enthalpic contributions (⌬H app ) rather than due to entropic contributions (⌬S app ), which are negative in each case (see Table 3).…”
Section: Selection Of Beclin 1 Residues Important For Binding To Bothmentioning
confidence: 99%